Omega-3 Fatty Acids for Major Depressive Disorder A Systematic Review - Newberry, Sydne (RAND Corporation, 2015)
RAND researchers conducted a systematic review that synthesized evidence from randomized controlled trials of omega-3 fatty acids-used adjunctively or as monotherapy-to provide estimates of their efficacy and safety in treating adults with major depressive disorder.